TRANSFORMASI IDENTITAS SOSIAL TENAGA KERJA INDONESIA (Studi Deskriptif Transformasi Identitas Sosial TKI Pasca Migrasi di Kelurahan Mojorejo, Kecamatan Karangmalang, Kabupaten Sragen ) - Innez Kartika Sari; Drajat Tri Kartono (Journal of Development and Social Change, 2018)
Abstract : Identity always changes frequently because identity is a part of human it self which always be changed. Identity changed to another form of identity they have had, it called identity transformation. It also occurs in Ex Indonesian Migrant Workers (TKI) in Mojorejo who used migration for transforming their social identity. The purpose of this study is to analyzed and described the process which occurred in social identity transformation of Indonesian Migrant Workers (TKI) in Mojorejo by Social Identity Transformation Theory which explaned by Jennifer Todd and Social Practices which explaned by Pierre Bourdieu for explaining the initial identity before migration and final identity after migration.This study is a single deskriptive study. Primary data were sources from informants by interview. Secondary data were sources from literatures, written documents, and archives. The informants were selected by purposive sampling. Informants were selected by key informan based on some requirement which determined by researcher ie the informant should be a citzens of Mojorejo Village, of Karangmalang district, of Sragen Regency and should have a citizen ID. Data validity was used triangulation by comparing observation data with interview data, comparing interview data from Eks TKI with interview data from citizen non TKI, and comparing interview data with secondary data were sources from literatures, written documents, and archives. Data analyzing technique was used interactive model analysis through data reduction, data presentation, drawing conclusion, and verification. This research describes social identity transformation which occured in ex Indonesian Migrant Workers (TKI) in Mojorejo by using Sosial Identity Transformation theory which explained by Jennifer Todd. This research shows the process of Social Identity Transformation in three stages of transformation, such as: dissonancy of habitus with social order, internal dissonancy, and moment of intentionally after taking a migration. From many several kinds of the result of Social Identity transformation, there was only partial kinds which occurred in Mojorejo they are : assimilation, conversion, and privatization.Keywords : Transformation, social identity, TKIAbstrak : Identitas senantiasa berubah mengingat identitas merupakan suatu hal yang ‘cair’. Perubahan dari suatu identitas menjadi identitas yang lain dinamakan transformasi identitas. Hal ini juga terjadi pada para Eks TKI di Kelurahan Mojorejo yang sengaja melakukan migrasi untuk merubah identitas sosialnya. Penelitian ini bertujuan menganalisis proses yang terjadi dalam transformasi identitas sosial tenaga kerja Indonesia di Kelurahan Mojorejo dengan teori Jennifer Todd Transformasi Identitas Sosial dan Piere Bourdeieu untuk menjelaskan identitas awal dan akhir dari proses transformasi tersebut. Penelitian ini merupakan studi Deskriptif. Data bersumber dari informasi yang diperoleh langsung dari informan, studi pustaka, dokumen tertulis dan arsip. Teknik pengumpulan data menggunakan wawancara dan observasi. Pemilihan informan dilakukan secara purposive sampling yaitu memilih narasumber berdasarkan persyaratan yang telah peneliti tentukan seperti merupakan warga Kelurahan Mojorejo, Kecamatan Karangmalang, Kabupaten Sragen dan sudah dewasa ditunjukkan dengan berumur diatas 17 tahun. Validitas data menggunakan trianggulasi sumber yskni dengan membandingkan data hasil pengamatan dengan data hasil wawancara, membandingkan hasil wawancara terhadap narasumber eks TKI dengan wawancara terhadap warga masyarakat bukan TKI, dan membandingkan hasil wawancara dengan dokumen buku dan jurnal yang berkaitan. Data dianalisis dengan model interaktif melalui reduksi data, penyajian data, penarikan kesimpulan dan verivikasi. Hasil penelitian menggambarkan adanya transformasi identitas sosial yang terjadi pada para Eks TKI di Kelurahan Mojorejo dengan menggunakan teori Transformasi Sosial oleh Jennifer. Dimana para Eks TKI mengalami tahap-tahap antara lain disonansi habitus dengan tatanan sosial, disonansi internal dan moment of intentionality setelah melakukan migrasi. Dari tahap-tahap tersebut muncul berbagai macam jenis asimilasi identitas baru dan identitas lama antara lain asimilasi, konfersi dan privatisasi.Kata Kunci : Transformasi, identitas sosial, TKI